The Ukrainian Crisis: Impact on Sino-Russian Relations - Kashin, Vasily (2016)
The Russian confrontation with the West over Ukraine from 2014 gave a boost to Sino-Russian relations. While China did take some steps to support Russia in this conflict, the Chinese ability to do so remains limited and strong interdependence has not been achieved.